A cucurbit[6]uril-carbon dot system: a potentially new bioimaging agent. (9th March 2022) - Zhang, Shuai; Tian, Yan; Liu, Ming; Hong-Meng, Tie; Li, Chun-Rong; Zeng, Xi; Xiao, Xin; Redshaw, Carl
Abstract : We report novel cucurbit[6]uril (Q[6])/carbon quantum dots (CQDs) prepared by solvothermal and nitrogen doped methods. Abstract : We report novel cucurbit[6]uril (Q[6])/carbon quantum dots (CQDs) prepared by solvothermal and nitrogen doped methods. The m -Q[6]-CQDs have been characterized by FTIR, XRD and X-ray photoelectron spectroscopy. The obtained m -Q[6]-CQDs exhibit good water dispersibility, photostability and strong blue fluorescence emission. The m -Q[6]-CQDs also showed good selectivity for metal ions. When Hg 2+ is present, the fluorescence is quenched, but upon the addition of Al 3+, the fluorescence is enhanced. It was also shown that the fluorescence of the m -Q[6]-CQDs can resist both the interference from other metal ions as well as high ionic strength environments. The m -Q[6]-CQDs were utilized for the optical bioimaging of human prostate cancer (PC-3) cells, and were found to exhibit both low cytotoxicity and excellent biocompatibility.